Dis-moi ce que tu manges... - France ARBOIX-CALAS
All the living beings share a function of nutrition that allows bringing the energy necessary for its survival. In humans, eating behavior that ensures the function of nutrition is influenced by several determinants on which education can act. The works undertaken in food education have as a finality to improve health of the individuals who are then perceived like "object" of education. In addition to the acquisition of basic knowledge to have a healthy food, the challenges of this food education can also relate to the emergence of a "subject eater". The purpose of this article is to change perspective and to make pass the eater of the statute of object to that of subject. The aim here is to define an educational framework in the field of education to food component of health education, allowing the emergence of a subject, that is to say, a being autonomous, free and responsible to his diet. This "subject eater" is distinguished then from an "object eater" which depends entirely on the external medium to feed and which is let handle by this one. After having identified the determinants accessible to education among those put at the day by various integrating models of food behavior, we will define levers of action for each one of these determinants. These levers make it possible to define a food education which consists finally less of the transmission of scientific knowledge that to the development of life skills.